Sustainable Development of Enterprises In COVID-19 In China - Jie Wan (International Journal of Management and Education in Human Development, 2022)
Novel coronavirus pneumonia came to the end of 2019, and the city blockade and industrial production basically collapsed. This has a great impact on China's macro economy and real estate industry. This paper takes China's real estate industry as the focus, analyzes the current situation of COVID-19's long-term development trend in China's real estate industry and the impact of the epidemic on real estate management, hoping to help China's real estate industry. Recognize the situation and finally promote the healthy and stable development of the real estate industry.